The Bio Immune(G)ene Medicine or How to Use a Maximum of Molecular Resources of the Cell for Therapeutic Purposes - Gilbert, Glady (Edelweiss Applied Science and Technology, 2019)
At a time when emerging concepts capable of revolutionizing old medical paradigms are flourishing, such as systems biology, integrative medicine or personalized medicine, it is of the utmost interest to observe how such concepts can be applied in the context of a therapeutic method that is both innovative and devoid of any undesirable effect, because it simply seeks to play a regulatory role. The aim of this method called Bio Immune(G)ene MEDicine (BI(G)MED) is to make the best use of all the molecular resources available to the cell to restore the homeostasis of the latter at its various levels of genome, epigenome, transcriptome, proteome and metabolome. To achieve this goal, it is of course essential to use means borrowed to nanobiotechnologies to ensure a high efficiency of the molecules made available to the cells to facilitate their selfregulation thanks to a therapeutic model essentially based on true biomimicry. The description of one or the other clinical case will show how this method can be effective in polypathologies, sometimes very advanced and often recurrent, without ever harming the patient elsewhere.